2014
DOI: 10.4067/s0718-33052014000200005
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of niobium carbide coatings produced on tool steels by thermoreactive deposition/diffusion

Abstract: RESUMENEn este trabajo se depositaron recubrimientos de carburo de niobio sobre aceros AISI M2, H13 y D2, utilizando la técnica de deposición por difusión termorreactiva. Los carburos se obtuvieron usando baños de sales compuestos por bórax fundido, ferroniobio, ferrovanadio y aluminio a una temperatura de 1.020 °C durante 4 horas. La presencia de los recubrimientos fue observada por microscopia electrónica de barrido. Las fases fueron determinadas usando difracción de rayos X, y se utilizó microdureza para de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Figure 10 shows the Nyquist diagrams obtained from the electrochemical impedance test performed on the niobium carbide coating submerged in biodiesel at a temperature of 291 ± 2 K with immersion times of 1 h, 24 h, 48 h, and 144 h. It was observed that the diagram was composed of two overlapping semicircles, suggesting the presence of two constant phase elements corresponding to two electrolyte-electrode interphases. The first, at high frequencies and a larger radius, is usually associated with the resistive-capacitive behavior of the coating; and the second time constant was related to the electrolyte-substrate interface due to the pores in the coating [24,25]. The polarization resistance decreased from 1.48 × 10 10 Ω to 8.95 × 10 9 Ω with an increase in the immersion time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 10 shows the Nyquist diagrams obtained from the electrochemical impedance test performed on the niobium carbide coating submerged in biodiesel at a temperature of 291 ± 2 K with immersion times of 1 h, 24 h, 48 h, and 144 h. It was observed that the diagram was composed of two overlapping semicircles, suggesting the presence of two constant phase elements corresponding to two electrolyte-electrode interphases. The first, at high frequencies and a larger radius, is usually associated with the resistive-capacitive behavior of the coating; and the second time constant was related to the electrolyte-substrate interface due to the pores in the coating [24,25]. The polarization resistance decreased from 1.48 × 10 10 Ω to 8.95 × 10 9 Ω with an increase in the immersion time.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of additional peaks related to NbO, NbO 2 , and Nb 2 O 5 was observed. The diffractograms showed that the two surfaces interacted with the biodiesel and that different species of oxides appeared, which were produced during the corrosion process [24]. The X-ray patterns made by the iron smelter before and after the biodiesel corrosion process are shown in Figure 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallographic planes are observed in orientations (111), (200) and (311), with crystal cubic system (Fm3m) and space group 225. As the layers are formed as a consequence of the direct combination of carbon in the steel with niobium dissolved in the bath, the presence of alloying elements in the steel does not have effect on the composition of the coatings [19]. Figure 2 shows SEM micrographs of the crosssection of the coatings produced on the tools.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…In many applications, tool steels are coated with transition metal carbides to improve corrosion resistance. Some authors report the improvement in the corrosion resistance of AISI D2 (111,112,113,114,115,116,117) and AISI H13 115) tool steel with the production of a layer of chromium niobium carbide on the steel surface, and other works have reported that for tool steels the corrosion behavior could be more influenced by its phase composition that the nanocrystalline structure (118) .…”
Section: Tool Steelsmentioning
confidence: 99%